2009
DOI: 10.1007/s10661-009-1197-x
|View full text |Cite
|
Sign up to set email alerts
|

Mullet and gudgeon liver histopathology and macroinvertebrate indexes and metrics upstream and downstream from a wastewater treatment plant (Febros River—Portugal)

Abstract: The increased pollution in ecosystems reinforces the importance of both chemical monitoring and biological monitoring of streams and rivers, as an effective water quality-based approach to assess aquatic ecosystem health. In this study, gudgeon (Gobio gobio) and mullet (Mugil cephalus) liver histopathology (biomarker) and some macroinvertebrate community indexes and metrics (bioindicator) were used to evaluate the effect of the wastewater treatment plant (WWTP) of Febros (Avintes) in Febros River water quality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Since the EU and Portuguese legislations consider these EDCs non-authorized compounds [38,39], their current presence in this environment is enigmatic. One credible source of APEOs in this area is imported materials, including raw materials, as many industries (including textile) in this region [40] may use these types of compounds inadvertently. It is also possible that APEOs present in several pesticide mixtures to help their environmental dispersion reach the estuary by lixiviation [4].…”
Section: Industrial Compoundsmentioning
confidence: 99%
“…Since the EU and Portuguese legislations consider these EDCs non-authorized compounds [38,39], their current presence in this environment is enigmatic. One credible source of APEOs in this area is imported materials, including raw materials, as many industries (including textile) in this region [40] may use these types of compounds inadvertently. It is also possible that APEOs present in several pesticide mixtures to help their environmental dispersion reach the estuary by lixiviation [4].…”
Section: Industrial Compoundsmentioning
confidence: 99%
“…During the maturation period, the yolk deposition stage occurs in hepatocytes characterized by enlarged size of hepatocytes and increased basophilic cytoplasmic granules, and nucleoli undergo hypertrophy. Hepatocyte binucleate was found to increase and sinusoids with well vascularization (Chakrabarti & Chatterjee, 2014;Rajeshkumar, 2015, Abdallah et al, 2013Pinto et al, 2010;Tayel et al, 2014;Yilmaz et al, 2016). GSI and HSI in Mullet fish has fluctuative value based on spesies and location (Abdalhafid & El-Mor, 2014;El-Halfawy et al, 2007;El-Boray et al, 2012;Ghaninejad et al, 2010;Hashemi et al, 2012;Karim, 2017;Maryam et al, 2011;Nahdi et al, 2008;Sulistiono et al, 2001;Mokhtar et al, 2015;Saoudi & Aun., 2014;Wigati & Syafei., 2013;Yones et al, 2016).…”
Section: Gonadosomatic Index (Gsi) Value and Hepatosomatic Index (Hsimentioning
confidence: 99%
“…Xie et al (2010b) reported that both male and female Gambusia affinis in the Hanxi River of southern China showed significant morphological changes that were likely due to heavy contamination from municipal wastewater. Pinto et al (2010) used a combination of liver histology in two fish species (Mugil cephalus and Gobio gobio), as well as macroinvertebrate indices to describe the impact of a wastewater treatment plant on the Febros River in Portugal. Breckels and Neff (2010) described behavioral changes that were observed in brown bullheads (Ameiurus nebulosus) chronically exposed to pollution in the Detroit River (USA).…”
Section: Wastewatermentioning
confidence: 99%